(3MGTjI Ydi TQM CTcGd GdJCSjS RGOg GdQhei (B((3ehSi Hf eMeO GdeJhaj SfI(B815)s - (3CHi GdaJM Hf GdgGOi CHi fUQ Hf CHi SYjO GdMSjfj GdYQGbi GdeOYh HeJGM GdSYjOis; (3TeS GdOjf eMeO Hf GTQa GdSeQbfOj,J (B600 (3g` ? s
(3ChdgG (B:s
(3GdMeO ddg GdebOQ ebGOjQ GdCTjGA HMceJg heUhQ JUGhjQ GdCTcGd s
(3BNQgG (B:s
(3hJJe GdcdGe bGFdjf GdMeO ddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B41 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B105s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQGdcJH GdeUQjI (B((3QjGVI (B26) s
Keywords: (3GdQjGVjGJs